2018
DOI: 10.1130/g40197.1
|View full text |Cite
|
Sign up to set email alerts
|

A new interpretation for the nature and significance of mirror-like surfaces in experimental carbonate-hosted seismic faults

Abstract: Highly reflective, continuous smooth surfaces, known as "mirror-like surfaces" (MSs), have been observed in experimental carbonate-hosted faults, which were sheared at both seismic and aseismic velocities. MSs produced during high-velocity friction experiments (>0.1 m s-1) are typically interpreted to be frictional principal slip surfaces, where weakening mechanisms are activated by shear heating. We reexamined this model by performing friction experiments in a rotary shear apparatus on calcite gouge, at seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
101
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(117 citation statements)
references
References 19 publications
(34 reference statements)
15
101
1
Order By: Relevance
“…Exhumed faults provide a record of thermal, chemical, and rheological changes to fault materials by earthquake processes (Niemeijer et al, 2012;Rowe and Griffith, 2015). Fault mirrors (FM), common in fault damage zones, track these phenomena at micro-to nanoscales (e.g., Siman-Tov et al, 2013;Ault et al, 2015;Kuo et al, 2016;Pozzi et al, 2018). FMs are thin (<1 mm) high-gloss, light-reflective slip surfaces comprising layered nanoparticles, and they have been observed in carbonate, quartzite, granite, chert, and hematite (e.g., Power and Tullis, 1989;Fondriest et al, 2013;Kirkpatrick et al, 2013;Siman-Tov et al, 2013;Evans et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exhumed faults provide a record of thermal, chemical, and rheological changes to fault materials by earthquake processes (Niemeijer et al, 2012;Rowe and Griffith, 2015). Fault mirrors (FM), common in fault damage zones, track these phenomena at micro-to nanoscales (e.g., Siman-Tov et al, 2013;Ault et al, 2015;Kuo et al, 2016;Pozzi et al, 2018). FMs are thin (<1 mm) high-gloss, light-reflective slip surfaces comprising layered nanoparticles, and they have been observed in carbonate, quartzite, granite, chert, and hematite (e.g., Power and Tullis, 1989;Fondriest et al, 2013;Kirkpatrick et al, 2013;Siman-Tov et al, 2013;Evans et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…FMs are thin (<1 mm) high-gloss, light-reflective slip surfaces comprising layered nanoparticles, and they have been observed in carbonate, quartzite, granite, chert, and hematite (e.g., Power and Tullis, 1989;Fondriest et al, 2013;Kirkpatrick et al, 2013;Siman-Tov et al, 2013;Evans et al, 2014). Field studies and low-to high-speed deformation experiments on rock and gouge indicate FMs form by different processes and at variable slip rates (Verberne et al, 2013;Siman-Tov et al, 2015;McDermott et al, 2017;Pozzi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…These observations strongly suggest that MSSs are not related to any dynamic weakening mechanisms, and that their seismic origin remains debatable at best. Rather, as pointed out by Pozzi et al [139], MSSs seem to demarcate a rheological discontinuity between an ultrafine-grained zone, which internally deforms via thermally-activated and grain-size dependent deformation mechanisms, i.e., the PSZ, and the adjacent, coarser-grained wall rock, which deforms by brittle processes (grain fracturing). The fact that patchy MSSs formed in LVF tests are found at different topographic levels throughout the PSZ (Figure 6a) indicate that they probably formed as isolated patches rather than as a single, through-going film.…”
Section: Mss-bearing Pszs As Indicators For Past Seismic Slip?mentioning
confidence: 89%
“…The role of effective normal stress, and of cumulative displacement, on the formation of (patchy) MSSs with progressive shear strain in LVF tests remains to be investigated. Pozzi et al [139] recently reported on the microstructural development of MSS-bearing PSZs with progressive shear strain in HVF experiments on simulated calcite faults (σn = 25 MPa, v up to 1.4 m/s). Using polished sections prepared normal to the slip vector they observed that, after an initial stage of slip (Σx ≈ 7 cm), sharp discontinuities develop which are In general, MSSs are characterized by extremely low surface roughness, especially in a direction parallel to the shear direction [136,137].…”
Section: Nanocrystalline Principal Slip Zones Formed In Fault-slip Exmentioning
confidence: 99%
“…It is found that a large number of nanoparticles are developed in fault zones (Cai et al, ; Carpenter et al, ; Chester et al, ; Fondriest et al, ; Huang et al, ; Siman‐Tov et al, ; Wang & Sun, ), and these nanoparticles are considered to be associated with fault weakening (De Paola, ; Han et al, ; Siman‐Tov et al, ). To verify the aforementioned notion, many friction experiments have been conducted in recent years, for example, by adding spherical nanoparticles (metallic oxides and carbonatites; Han et al, ) or fault gouges to experimental faults (De Paola et al, ; Fondriest et al, ; Han et al, ; Pozzi et al, ; Siman‐Tov et al, , ; Zhang & He, ). The high‐velocity rotary shear experiments results show that spherical nanoparticles can lubricate the faults and reduce the friction dramatically at the onset of fault sliding, thus weakening the faults (De Paola et al, ; Han et al, , ; Siman‐Tov et al, ).…”
Section: Introductionmentioning
confidence: 99%